Odpowiedzi

2009-11-14T16:11:43+01:00
1) 2 \*√3 ............2√3 .......... 2√3
------------ ...... = ------------- = ........ ----------
3√3 \*√3...........3*3..............9


2) 2-√2..... \*(1-√3) ...... 2-√2(1-√3).......... 2-2√3-√2+√6
-------- ..... = ..... ------------ ... = ... --------------
1+√3 \*(1-√3)........... 1 - 3.................... -2
2009-11-14T16:12:20+01:00
2/3√3=2*√3 / 3√3 * √3= 2√3/9

2-√2 / 1 +√3 = (2-√2) * (1-√3) / (1+√3) * (1-√3) = 2-2√3-√2+√6 / -2




2009-11-14T16:15:24+01:00
2 2X3√3 6√3
____=___________=__________
3√3 3√3x3√3 27




2-√2 (2-√2)x(1-√3) 2- 3√3-√2+ √6
_______=________________=______________
1+√3 (1+√3) x (1-√3) 1-3